Metabolically Healthy Obesity is not a Myth. Issue 2 (24th February 2023) - Farabi, Sarah S; Smith, Gordon I; Yoshino, Jun; Klein, Samuel
Abstract: People with obesity who do not have the metabolic syndrome or components of the metabolic syndrome have been characterized as having metabolically healthy obesity (MHO). However, the existence of MHO has been questioned because people with MHO are at greater risk of developing diabetes and fatal cardiovascular disease than people who are lean and healthy. Here we report findings from a 25-year-old woman with rigorously defined MHO (normal oral glucose tolerance, insulin sensitivity [assessed using the hyperinsulinemic-euglycemic clamp procedure], plasma triglyceride, and intrahepatic triglyceride content) evaluated at baseline (body mass index, 37.7 kg/m 2 ) and 5 years later, after a 32% (30.8 kg) increase in body mass (BMI, 49.6 kg/m 2 ). Weight gain did not have adverse effects on fasting plasma glucose, oral glucose tolerance, β-cell function, insulin sensitivity, plasma triglyceride, intrahepatic triglyceride content, or carotid intima-media thickness. Adipose tissue expression of genes involved in extracellular matrix formation remained unchanged. Adipose tissue expression of several inflammation-related genes increased by more than 30%, but was not associated with a corresponding increase in plasma cytokine concentrations, with the exception of IL-6 and C-reactive protein. The present case study demonstrates that some people with obesity are resistant to the adverse cardiometabolic effects of excess adiposity and marked weight gain.